A contribution to the Mutillidae (Hymenoptera) of Hong Kong - Barthélémy, Christophe; Lelej, Arkady S.; Loktionov, Valery M. (Zootaxa, 2018)
A list of 12 species in nine genera occurring in Hong Kong is given. The hitherto unknown male of Bischoffitilla lamellata (Mickel, 1933) is described and illustrated. Six species are newly recorded from Hong Kong. The current number of known mutillid species of Hong Kong is doubled from six to 12.